Juridical Review of Legal Protection of Patients' Personal Data in Health Services - Mahroni, Mahroni; Santoso, Aris Prio Agus; Guntara, Peter (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Indonesia is one of the countries that until now does not have a law that specifically regulates the protection of personal data. Lately, there are many cases in the community regarding the misuse of personal data. Especially with the ease with which people access the internet, so that the misuse of personal data through electronic media will spread rapidly. In the field of health services, personal data of patients cannot be separated from the possibility of misuse. It will be even more dangerous if the personal data is a track data of the patient's medical record which is very confidential.  The research method used is normative juridical, the approach method is more emphasized on the law, the source of legal material is the law, and the type of collection of legal materials is literature study. The results of this study are the use of Information and Communication Technology (ICT) in health services aimed at improving access, efficiency, effectiveness, and quality of medical processes involving medical service organizations in hospitals, clinics, health centers, medical practitioners both doctors and therapists, laboratories, pharmacies, insurance also involves patients as consumers. However, in the service process using the E-health program will collect a number of consumer personal data which is sensitive personal data and raises new legal problems, namely the extent to which health service providers can protect patients' personal data, which can be accessed, disseminated more easily through ICT advances. Until now, the existing regulations (existing law) have not provided maximum protection for patient's personal data because the regulation is still sectoral and scattered in several laws and regulations.